Construct Reconceptualization of Tourism Accessibility: Integrating Transportation Modes, Road Networks, and Parking Facilities to Explain Tourist Visits - Tahta Aunillah; Wachdijono (Indonesian Journal of Advanced Research, 2026)
Tourist visits are the main driver of the tourism business.  Therefore, many efforts are made to increase tourist visits, but many factors affect it. This study aims to analyze the influence of transportation modes, road networks, and parking facilities on the accessibility of tourist sites and their impact on tourist visits at Agrotourism Sangkanika Edugarden. The study used a quantitative approach with a survey method of 131 tourists in April-May 2026. Data were collected via a Likert-scale questionnaire and analyzed using Structural Equation Modeling and the Bootstrap method. The results of the study found that there was a reconceptualization of the construct, where the model became more parsimonious and fit; namely, the accessibility of tourist sites had a significant effect on tourist visits (b=0.921; p<0.05). The findings are also novel, so this research is very useful because it contributes to the development of accessibility theory, the use of discriminatory (methodological) tests, and, practically, for agrotourism managers to increase the number of tourist visits.